2020
DOI: 10.3390/molecules25071653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilberry Supplementation on Metabolic and Cardiovascular Disease Risk

Abstract: Metabolic syndrome is a cluster of interrelated conditions that is associated with an increased risk of cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). Oxidative stress may impair normal physiological functions, leading to various illnesses. T2DM is considered to be associated with increased oxidative stress, inflammation, and dyslipidemia, which may play a significant role in the development of cardiovascular complications, cancer and vision loss through cataracts and retinopathy. While conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 97 publications
0
31
0
Order By: Relevance
“…To address whether the observed protection was a chemical neutralization of the H 2 O 2 effect outside the cells, or if the berry compounds induced a biological response inside the yeast cells leading to a phenotype with enhanced stress resistance, two more experiments were performed: (1) cultivation of yeasts in the presence of digested extract followed by removal of the extract before the stress assay and (2) cultivation of yeasts without extract followed by addition of the digested extract before the stress assay. For these experiments, bilberry was selected, since prior work suggested that bilberry anthocyanins may reduce oxidative damage as well as inflammation in humans [ 25 , 26 , 27 , 28 , 29 ]. Results showed that the cells grown in yeast medium plus digested extract displayed a significantly higher stress resistance ( Figure 5 A) compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…To address whether the observed protection was a chemical neutralization of the H 2 O 2 effect outside the cells, or if the berry compounds induced a biological response inside the yeast cells leading to a phenotype with enhanced stress resistance, two more experiments were performed: (1) cultivation of yeasts in the presence of digested extract followed by removal of the extract before the stress assay and (2) cultivation of yeasts without extract followed by addition of the digested extract before the stress assay. For these experiments, bilberry was selected, since prior work suggested that bilberry anthocyanins may reduce oxidative damage as well as inflammation in humans [ 25 , 26 , 27 , 28 , 29 ]. Results showed that the cells grown in yeast medium plus digested extract displayed a significantly higher stress resistance ( Figure 5 A) compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reviews and meta-analyses have compared studies without accounting for differences in intervention formulations, which emerge when working with, for example, fresh berries, berry juices, dealcoholized wine and extracts [ 10 , 13 , 14 ]. Differences in intervention formulations would be expected to affect the bioavailability of polyphenols, similar to the way in which food matrices affect bioavailability, uptake and metabolism [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher dietary intakes of anthocyanins and catechins have been associated with a significantly lower risk of T2DM in 60,586 women over a 20-year observation period [ 9 ]. Bilberries are one of the richest natural sources of anthocyanins [ 10 , 11 ], whereas grape seeds contain the highest levels of total procyanidins and procyanidin dimers in fruits and vegetables [ 12 ]. However, previous studies evaluating the anti-diabetic and cholesterol-lowering effects of bilberry and grape seed extracts in humans have been inconclusive, mainly due to a large variability in outcomes within and between study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Bilberries have been observed to hold a plentitude of health-promoting properties. Research studies support their beneficial effects, among which antioxidant, anti-obesity, anticarcinogenic, cardioprotective, anti-inflammatory, hypoglycemic, antimicrobial, and vision improvement [12][13][14].…”
Section: Introductionmentioning
confidence: 98%